2008 International Conference on BioMedical Engineering and Informatics 2008
DOI: 10.1109/bmei.2008.181
|View full text |Cite
|
Sign up to set email alerts
|

Fuzzy Logic based Identification of Operator Functional States Using Multiple Physiological and Performance Measures

Abstract: This paper assesses the operator functional state (OFS) based on a collection of psychophysiological and performance measures. Two types of adaptive fuzzy models, namely ANFIS (adaptive-network-based fuzzy inference system) and GA (genetic algorithm) based Mamdani fuzzy model, are employed to estimate the OFSs under a set of simulated process control tasks involved in an automation-enhanced cabin air management system (aCAMS). The adaptive fuzzy modelling procedures are described and then validated using real-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 8 publications
0
11
0
1
Order By: Relevance
“…There are few studies employing NFS for MWL estimation. In studies by Zhang et al and Ting et al [53,58,59], a Genetic Algorithm (GA)-based Mamdani fuzzy model was used to optimize the FIS parameters. Here, 7.5 min intervals were used, with features from an EEG and cardiac sensor.…”
Section: Multimodal Fusion For Inferring Mwlmentioning
confidence: 99%
See 1 more Smart Citation
“…There are few studies employing NFS for MWL estimation. In studies by Zhang et al and Ting et al [53,58,59], a Genetic Algorithm (GA)-based Mamdani fuzzy model was used to optimize the FIS parameters. Here, 7.5 min intervals were used, with features from an EEG and cardiac sensor.…”
Section: Multimodal Fusion For Inferring Mwlmentioning
confidence: 99%
“…An extension of this work was further presented in a study conducted by Wang et al [46], with 2 min intervals, using Differential Evolution (DE) and Differential Evolution Algorithm with Ant Colony Search (DEACS) as means to optimize the ANFIS parameters. Zhang et al and Wang et al [46,58,59] demonstrated good results in an offline calibration and validation with the aforementioned models. Nevertheless, they also implemented a conventional ANFIS model for comparison, which showed poor results.…”
Section: Multimodal Fusion For Inferring Mwlmentioning
confidence: 99%
“…Серед найбільш поширених методів, які дозволяють проводити оцінку ФС операторів, можна виділити методи визначення обсягу короткочасної пам'яті, швидкості сприйняття інформації, інтенсивності уваги, точності і тривалості відтворення інтервалів часу, лабільності нервової системи [1], а також методи визначення значень психофізіологічних характеристик оператора, оцінки якості діяльності та надійності системи, показників активності підсистем організму людини (за даними вимірювання температури, електропровідності біологічно активних точок (БАТ), електрофізіологічних показників (ЕКГ, ЕМГ та ін.)) [2][3][4].…”
Section: аналіз літературних даних і постановка проблемиunclassified
“…If HRV 1 is to be effective as a marker of mental effort, stress or strain, it is expected that it shows a progressive reduction with the increment of workload. Here the HR is taken as the average of heart rate every minute, while HRV 2 is defined as the ratio between the standard deviation and mean value of HR data segment of 1 min (Wilson 1999;Zhang et al 2008b):…”
Section: Ofs Feature Extractionmentioning
confidence: 99%